2005
DOI: 10.1103/physrevb.71.233403
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and electronic structures of the (5, 3) single-walled gold nanotube from first-principles calculations

Abstract: The geometrical and electronic structures of the 4Å diameter perfect and deformed (5, 3) single-walled gold nanotube (SWGT) have been studied based upon the density-functional theory in the local-density approximation (LDA). The calculated relaxed geometries show clearly significant deviations from those of the ideally rolled triangular gold sheet. It is found that the different strains have different effects on the electronic structures and density of states of the SWGTs. And the small shear strain can reduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…11 Furthermore, they have also synthesized a single-wall helical gold nanotube with a smaller diameter of 0.4 nm in a UHV-TEM. 7 Such single-wall helical nanotubes and helical multishell nanowires have been intensively fabricated experimentally and investigated theoretically not just for Au 1,[5][6][7][11][12][13][14][15][16] but also for various metals (e.g., Ag, Pt, Na, Rh, Zr, Ti, Pb, and ferromagnetic Ni). 2,3,[17][18][19][20][21][22][23][24] These studies have reported that the nanotubes and nanowires possess distinct mechanical and electronic properties originating from their helical shell structure, including superplasticity, 3 quantum ballistic conductance, 4 and helical conduction channels (which potentially could be used to fabricate nanosolenoid).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, they have also synthesized a single-wall helical gold nanotube with a smaller diameter of 0.4 nm in a UHV-TEM. 7 Such single-wall helical nanotubes and helical multishell nanowires have been intensively fabricated experimentally and investigated theoretically not just for Au 1,[5][6][7][11][12][13][14][15][16] but also for various metals (e.g., Ag, Pt, Na, Rh, Zr, Ti, Pb, and ferromagnetic Ni). 2,3,[17][18][19][20][21][22][23][24] These studies have reported that the nanotubes and nanowires possess distinct mechanical and electronic properties originating from their helical shell structure, including superplasticity, 3 quantum ballistic conductance, 4 and helical conduction channels (which potentially could be used to fabricate nanosolenoid).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the magnetism is expected to be strongly dependent on the tube chirality, because the nanotubes with different chiralities have different electronic states. 1,2,12,18 Thus, studying ferromagnetic nickel nanotubes should lead to a deeper understanding of magnetism in nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery of the W@Au 12 icosahedral , cluster, the Au 20 tetrahedral cluster, and the gold nanotube, the idea emerged that a cagelike structure for gold could exist. In particular, the Au 32 fullerene system ( I h ) was first predicted from high-level quantum chemical calculations by Johansson et al and confirmed by Gu et al Its cagelike hollow structure was ascribed to the relativistic character of its electrons, to its icosahedral symmetry, and to a 4-fold degenerate HOMO, which prevents any Jahn−Teller distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nanowire was found to be composed of 5:3 nanotube, which are composed of five atomic rows. Further, the electronic and geometrical structure of the gold nanotube (5:3) was expounded by the Yang et al [68].…”
Section: Synthesis Of Gold Nanotubesmentioning
confidence: 99%
“…Further, the electronic and geometrical structure of the gold nanotube (5:3) was expounded by the Yang et al. [68].
Figure 12.The structural properties of a nanotube: (a) T = 500 K, (b) T = 900 K. These top views of the central part of a nanotube are represented by the particle trajectory plots and refer to a time span of 3.5 ps.
…”
Section: Synthesis Of Gold Nanotubesmentioning
confidence: 99%